2015
DOI: 10.1182/blood-2014-04-568170
|View full text |Cite
|
Sign up to set email alerts
|

Notch1 acts via Foxc2 to promote definitive hematopoiesis via effects on hemogenic endothelium

Abstract: Key Points Notch1 induction promotes specification of hemogenic endothelial cells during embryonic stem cell differentiation. Foxc2 functions downstream of Notch in specification of hemogenic endothelium in mouse and zebrafish embryos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 58 publications
4
48
0
Order By: Relevance
“…Indeed, most of the emerging hemogenic endothelial cells as defined by Sca1-GFP are also phospho-CREB + . Interestingly, activation of PKA results in up-regulation of Foxc2, which has been recently identified to play a role in the hemogenic endothelium (Jang et al, 2015). The endothelial-tohematopoietic transition has garnered recent interest because lineage tracing and live-imaging studies have shown that HSCs emerge from the VE-cadherin + vascular endothelium in the AGM (Chen et al, 2009;Bertrand et al, 2010;Boisset et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, most of the emerging hemogenic endothelial cells as defined by Sca1-GFP are also phospho-CREB + . Interestingly, activation of PKA results in up-regulation of Foxc2, which has been recently identified to play a role in the hemogenic endothelium (Jang et al, 2015). The endothelial-tohematopoietic transition has garnered recent interest because lineage tracing and live-imaging studies have shown that HSCs emerge from the VE-cadherin + vascular endothelium in the AGM (Chen et al, 2009;Bertrand et al, 2010;Boisset et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Relative to the FL and BM, the AGM is enriched in IL-3 and IL-6 signaling pathways, 3,24 which in concert with other pathways such as Notch signaling, participate in hematopoietic emergence. 19,43 The AGM is enriched for shear-stress-mediated PGE2 and protein kinase A/cAMP-responsive element-binding protein signaling, [44][45][46] which can activate IL-6. [47][48][49] Subsequently, through exposure to IFN-a during maturation in the FL, AGM HSCs acquire expanded potential for engraftment in adults.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] Notch2 knockouts show no obvious hematopoietic defects 33 and Notch3 and Notch4 knockouts are viable, indicating their nonessential role in HSC development. 43,47 The requirement for Notch in the endothelial-hematopoietic transition is conserved in zebrafish, 19,[48][49][50][51] where Notch1 acts through activation of and cooperation with important transcription factors such as Gata2, Runx1, Scl, Foxc2, and Hes1/5. 34,48,[50][51][52][53][54] Although Notch is essential for early HSC development, exact stage-specific requirements for this signaling pathway in this multistep maturation process remain unclear.…”
Section: Introductionmentioning
confidence: 99%